Madrasah Head Transformational Leadership Strategy in Improving Teacher Professionalism - Dewi Yanti (Universitas Muhammadiyah Palu, 2024)
The head of a madrasah who is able to carry out leadership transformation means that he can turn the potential of his institution into energy to improve the quality of student learning processes and outcomes. Potential cannot develop without the role and function performed by a leader. The implementation of transformational leadership will facilitate the efforts of madrasah heads to accelerate or accelerate the capacity growth of teachers in building themselves, working smarter, and even harder to realize madrasah reform. This study aims to determine the Transformational Leadership Strategy of Madrasah Heads in Improving Teacher Professionalism. The results of the study showed that the strategies carried out by the head of the madrasah in improving teacher professionalism were: 1) Organize the implementation of activities that can improve the performance of educators, 2) Identify problems that occur, 3) Provide rewards and sanctions, 4) Hold meetings between subject educators Subject Teacher Deliberation (MGMP), Increase discipline for all educators, staff, and students in learning, 6) Evaluate difficulties related to educator performance, , Continue to strive for welfare for all educators and staff, Creating comfort (harmony) in the work environment. So from several steps that have been and are being carried out by the head of the madrasah it is proven to be able to improve teacher professionalism in learning.